Investigation of vertical carbon nanosheet growth and its potential for microsupercapacitors. Issue 1 (March 2021) - Velasco, A.; Vyas, A.; Wang, K.; Li, Q.; Smith, A. D.; Lundgren, P.; Enoksson, P.
Abstract: One of the biggest applications that are coming with the Internet of Things (IoT) are miniaturized sensor networks that connect wirelessly to each other and the internet. Microsupercapacitors (MSCs) are ideal to power these devices, with large cyclability and lifetime. Porous carbons are the material of choice for these devices, but their morphology and manufacturing are far from optimized. Vertically oriented graphene MSCs have shown great promise due to their high specific surface areas and conductivity. In this work, the growth of vertically aligned carbon nanosheets (CNS) on 2-inch wafers has been studied, and it has been used as active material to manufacture MSC and transmission line model (TLM) wafers. The fabricated CNS MSC devices show a capacitance of 7.4 μF (50.7 μF/cm 2, normalized to the area of the electrodes), a five-times increase from previous results obtained by the group.